2022
DOI: 10.1039/d2fo01935c
|View full text |Cite
|
Sign up to set email alerts
|

Whey protein and soy protein prevent obesity by upregulating uncoupling protein 1 to activate brown adipose tissue and promote white adipose tissue browning in high-fat diet-fed mice

Abstract: There are inconsistent conclusions regarding the effect of whey protein and soy protein supplementation on obesity, and the underlying mechanisms of a high-protein diet for weight loss remain to be...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The ingredients of the experimental diets have been reported in our previous study. 14 After feeding for 12 weeks, all mice were fasted for 12 hours and anesthetized with 3% sodium pentobarbital via intraperitoneal injection, and blood was obtained through enucleating the eyeball. Then, the mice were sacrificed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The ingredients of the experimental diets have been reported in our previous study. 14 After feeding for 12 weeks, all mice were fasted for 12 hours and anesthetized with 3% sodium pentobarbital via intraperitoneal injection, and blood was obtained through enucleating the eyeball. Then, the mice were sacrificed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study reported the result of the ITT, indicating that SPI could better improve insulin sensitivity relative to WPI. 14 Effect of WPI and SPI on weight of the liver and gastrocnemius muscle Macroscopic observation indicated that the livers of the SPI groups were more bright red in color compared with the WPI groups (Fig. 1A).…”
Section: Effect Of Wpi and Spi On Ir-related Parametersmentioning
confidence: 98%
See 3 more Smart Citations